Alkene, Bromide, and ROH – How To Achieve Selectivity? Electrochemical Synthesis of Bromohydrins and Their Ethers. Issue 12 (6th May 2021) - Bityukov, Oleg V.; Vil', Vera A.; Nikishin, Gennady I.; Terent'ev, Alexander O.
Abstract: Bromohydrins and their ethers were electrochemically synthesized via hydroxy‐ and alkoxybromination of alkenes using potassium bromide and water or alcohols. High selectivity of bromohydrins formation was achieved only with the use of DMSO as the solvent and an acid as the additive. The proposed combination of starting reagents, additives, and solvents allowed to form bromohydrins or their ethers selectively despite the variety of side‐products (epoxides, dibromides, diols). Bromohydrins were obtained in high yields, up to 96%, with a broad substrate scope in an undivided electrochemical cell equipped with glassy carbon and platinum electrodes at high current density. Abstract :